Unraveling Massive Crocins Transport and Accumulation through Proteome and Microscopy Tools during the Development of Saffron Stigma - Gómez Gómez, Lourdes (2017)
Crocins, the glucosides of crocetin, are present at high concentrations in saffron stigmas and accumulate in the vacuole. However, the biogenesis of the saffron chromoplast, the changes during the development of the stigma and the transport of crocins to the vacuole, are processes that remain poorly understood. We studied the process of chromoplast differentiation in saffron throughout stigma development by means of transmission electron microscopy. Our results provided an overview of a massive transport of crocins to the vacuole in the later developmental stages, when electron dense drops of a much greater size than plastoglobules (here defined “crocinoplast”) were observed in the chromoplast, connected to the vacuole with a subsequent transfer of these large globules inside the vacuole. A proteome analysis of chromoplasts from saffron stigma allowed the identification of several well-known plastid proteins and new candidates involved in crocetin metabolism. Furthermore, expressions throughout five developmental stages of candidate genes responsible for carotenoid and apocarotenoid biogenesis, crocins transport to the vacuole and starch metabolism were analyzed. Correlation matrices and networks were exploited to identify a series of transcripts highly associated to crocetin (such as 1-Deoxy-d-xylulose 5-phosphate synthase (DXS), 1-Deoxy-d-xylulose 5-phosphate reductoisomerase (DXR), carotenoid isomerase (CRTISO), Crocetin glucosyltransferase 2 (UGT2), etc.) and crocin (e.g., ζ-carotene desaturase (ZDS) and plastid-lipid-associated proteins (PLAP2)) accumulation; in addition, candidate aldehyde dehydrogenase (ADH) genes were highlighted. View Full-Text